Sistem Smart Garden Tanaman Bayam Menggunakan Metode Fuzzy Logic - Alfitri, Nadia; Efrizon, Efrizon; Kurniadi, Dedi; Nufus, Cindy Dahrun; Hidayat, Anton (Teknik Elektro Politeknik Negeri Padang, 2023)
Treatment of Spinach, even though it has been given fertilizer, also keep on eye to monitor lots of water when watering. If the soil is too wet it will interfere with the absorption of nutrients needed for spinach growth. The use of technology makes it easy to monitor and control the condition of spinach plants in real time. Good soil moisture for spinach plants is in the range of 45% equivalent to a voltage value of 2.78 Volts to 60% which is equivalent to a voltage value of 2.03V. Meanwhile, soil that is suitable for growing spinach is soil that has a pH between 6-7. Mamdani fuzzy logic method is applied to a microcontroller as a reference in making decisions to regulate the speed of the water pump. There are five levels of pump speed for automatic watering of spinach from very fast to very slow to maintain stable soil moisture. Based on the test results, it is proven that the system can work correctly using Mamdani fuzzy with an error of 0.023%.